The Implementation of Make-a-Match Cooperative Learning in Improving Elementary Students’ Cognitive Engagement in Islamic Cultural History Learning - Jasuli; Ulfa, Maria; Mulyono, Muhammad Riski (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the implementation of Make-a-Match cooperative learning in improving elementary students’ cognitive engagement in Islamic Cultural History (Sejarah Kebudayaan Islam/SKI) learning. The research focuses on examining the planning, implementation, and evaluation processes of the learning strategy and its impact on students’ participation, interaction, and understanding during classroom activities. This study employed a qualitative descriptive approach conducted at MI Ar-Roudhoh Patrang Jember, Indonesia, involving one Islamic Cultural History teacher and 26 fifth-grade students. Data were collected through classroom observations, semi-structured interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña. Data validity was ensured through source and technique triangulation. The findings revealed that the implementation of Make-a-Match cooperative learning significantly improved students’ cognitive engagement and classroom participation. During the learning process, students actively participated in collaborative activities, including searching for matching cards, discussing concepts, answering questions, and explaining historical materials. The method also increased students’ motivation, communication skills, and conceptual understanding of the exemplary story of Uthman bin Affan. In addition, students’ daily test scores improved after the implementation of the cooperative learning strategy, with most students achieving scores above the minimum mastery criterion (Kriteria Ketuntasan Minimal/KKM). The novelty of this study lies in its focus on cognitive engagement within Islamic Cultural History learning at the elementary madrasah level. This study contributes theoretically to the discourse of cooperative learning and student engagement in Islamic education while practically offering an innovative instructional strategy for creating interactive, student-centered, and meaningful learning environments.